1999
DOI: 10.1002/(sici)1097-0274(199904)35:4<390::aid-ajim10>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory protective devices: Rates of medical clearance and causes for work restrictions

Abstract: Background There are no published data on the outcomes and benefits of medical evaluations for the use of respiratory protective devices. We, therefore, conducted a retrospective database and chart review to assess the rates of medical clearance and causes for work restrictions at a Department of Energy complex. Methods All workers with work restrictions or denied clearance over a one‐year period were identified and their medical records abstracted. Results Of the 5,569 workers who received medical evaluation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…(28) The use of spirometry and physical examination were found to add little to the detection of relevant medical conditions for clearance to use a respirator. (29) Although screening for musculoskeletal disorders is advocated as a way to reduce workers' compensation costs (30), existing screening policies are rarely based on data showing appropriate diagnostic yield or cost-benefit. In a systematic review of assessment for fitness for work, Serra (31) found general confusion about the decision-making process used to judge fitness for work, and very scarce scientific evidence based on empirical data to support current practices.…”
Section: Discussionmentioning
confidence: 99%
“…(28) The use of spirometry and physical examination were found to add little to the detection of relevant medical conditions for clearance to use a respirator. (29) Although screening for musculoskeletal disorders is advocated as a way to reduce workers' compensation costs (30), existing screening policies are rarely based on data showing appropriate diagnostic yield or cost-benefit. In a systematic review of assessment for fitness for work, Serra (31) found general confusion about the decision-making process used to judge fitness for work, and very scarce scientific evidence based on empirical data to support current practices.…”
Section: Discussionmentioning
confidence: 99%
“…When personal protective equipment may be required to control exposure, temporary reassignment should be considered in most of the above scenarios if there is a significant exposure to a known reproductive hazard because PPE may not offer perfect protection and because there are limited data on respirator use during pregnancy. 35 Temporary reassignment should also be considered when an individual's medical history or risk factors suggest a need.…”
Section: Temporary Reassignmentmentioning
confidence: 99%
“…71 From a U.S. regulatory perspective, the OSHA CFR 1910.124 regulation governing respiratory protection in the workplace does not ask about pregnancy in its mandatory medical questionnaire. 11 Leakage into the breathing zone while wearing an N95 FFR can occur (1) through the filter media itself, (2) at the face=N95 FFR interface, and (3) from other components of the respirator (e.g., exhalation valve); the combined leakage is termed total inward leakage. 72 Optimal protection from an N95 FFR requires that the respirator selected fits the wearer appropriately so as to minimize leakage at the face=N95 FFR interface.…”
Section: Regulatory Issuesmentioning
confidence: 99%
“…9 However, there is little reliable information or guidance regarding the use of FFRs during pregnancy. 7,10,11 Further, there are numerous inconsistent or contradictory statements about this topic. For example, a Canadian worker safety guideline 12 from the province of Alberta's Department of Employment, Immigration, and Industry stipulates that ''pregnant workers with lower than normal pulmonary function should be carefully assessed as to their fitness to use respirators because of concerns that the diaphragmatic elevation during pregnancy and the increased oxygen demand of pregnancy produce a trend toward the likelihood of respiratory fatigue while wearing some respirators,'' 12 whereas another guideline 13 from the same agency, addressing the medical assessment of respirator users, does not mention pregnancy.…”
Section: Introductionmentioning
confidence: 99%